Additives to petroleum bitumen from brown coal of Ukraine - Lysenko, Liudmyla; Bogoyavlenska, Olena; Miroshnichenko, Denis; Miroshnychenko, Mykhailo; Pyshyev, Serhiy; Chipko, Taras; Donchenko, Myroslava; Prysiazhnyi, Yuriy (Національний технічний університет "Харківський політехнічний інститут", 2024)
It is known that there are significant deposits of lignite (brown coal) in Ukraine. Therefore, new methods of using lignite and processing its products are necessary. The latter includes humic acids. The main reason for adding humic acids to road bitumen under the specified conditions is to improve its resistance to technological aging compared to the original binder.
Keywords: raw material base; technological processes; components of boiler fuel; quality characteristics; humic acids; interaction; дослідження; переробка; дорожній бітум; стійкість; буре вугілля; модифікація